1999
DOI: 10.1046/j.1365-2273.1999.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of six weeks topical nasal betamethasone drops on the hypothalamo-pituitary-adrenal axis and bone turnover in patients with nasal polyposis

Abstract: Betamethasone topical nasal drops may have systemic corticosteroid activity and cause suppression of the hypothalamo-pituitary-adrenal (HPA) axis and impairment of bone turnover. The aim of this study was to assess the effect of a standard 6-week regime of betamethasone topical nasal drops on the HPA axis (using a physiological dose (1 microg) ACTH test) and on bone turnover (using markers of bone turnover, urinary deoxypyridinoline and serum bone specific alkaline phosphatase). Eleven patients with nasal poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Topical intranasal corticosteroids act directly on the nasal mucosa to produce optimal effects, but older trials have shown that dexamethasone, beclomethasone, and betamethasone may induce moderate adrenal suppression . The primary response of corticosteroids on the hypothalamic pituitary axis is negative feedback caused by suppression of corticotrophin‐releasing hormone and adrenocorticotropic hormone levels, resulting in decreased cortisol secretion .…”
Section: Discussionmentioning
confidence: 99%
“…Topical intranasal corticosteroids act directly on the nasal mucosa to produce optimal effects, but older trials have shown that dexamethasone, beclomethasone, and betamethasone may induce moderate adrenal suppression . The primary response of corticosteroids on the hypothalamic pituitary axis is negative feedback caused by suppression of corticotrophin‐releasing hormone and adrenocorticotropic hormone levels, resulting in decreased cortisol secretion .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized double‐blind study by Fowler et al., in patients with nasal polyposis, showed suppression of the HPA axis following an 8‐week course of betamethasone drops but a similar length course with fluticasone nasules had no effect. A further study by the same team also showed that 6 weeks of treatment with the recommended dose of intranasal betamethasone drops suppressed the HPA axis . However, beclomethasone dipropionate nasal spray is not associated with any suppressive effect on the HPA axis in both adults and children and does not produce systemic side effects, even with prolonged use of up to 6 years…”
Section: Discussionmentioning
confidence: 96%
“…Many intranasal steroid preparations have been studied including prednisolone acetate nasal spray, fluticasone propionate spray and nasules, triamcinolone acetonide spray, mometasone furoate spray, fluticasone furoate spray, beclomethasone dipropionate spray, betamethasone nasules, budesonide spray and respules, and budesonide respules added to saline irrigations . Few studies have shown any measurable impact on the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Betamethasone drops have effectively been used for the treatment of nasal polyps, but there was considerable suppression of the hypothalamic-pituitary-adrenal axis. 7 Recently, fluticasone propionate nasal drops (FPNDs), Nasules (GlaxoSmithKline, Brentford, Essex, United Kingdom), have become available for the treatment of polyposis. These have a low bioavailability and fixed dosage volume to achieve controlled administration.…”
mentioning
confidence: 99%